2022
DOI: 10.1371/journal.pone.0277385
|View full text |Cite
|
Sign up to set email alerts
|

Impact of secondary mitral regurgitation on survival in atrial and ventricular dysfunction

Abstract: Background Natural history of atrial and ventricular secondary mitral regurgitation (SMR) is poorly understood. We compared the impact of the degree of SMR on survival between atrial and ventricular dysfunction. Methods We conducted a retrospective cohort study of patients who underwent echocardiography in a healthcare network between 2013–2018. We compared the survival of patients with atrial and ventricular dysfunction, using propensity scores developed from differences in patient demographics and comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Moderate or severe MR is found in 2.3% of older adults, 19 of whom approximately two-thirds have functional MR. 1 Among those with functional MR, 60% are of ischemic etiology. 1 , 20 This already high number of patients with severe iMR seeking treatment is likely to further increase with the recent Food and Drug Administration approval of the MitraClip for severe secondary MR, 21 similar to the impact of the adoption of transcatheter aortic valve replacement and its “halo” effect on surgical aortic valve replacement volume. 22 In multidisciplinary evaluation, the practical use of our risk stratification algorithm may be as the first broad-stroke identification of the low-risk group, which is expected to do very well from surgery, and separating them from the high-risk group, which likely would have poor surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate or severe MR is found in 2.3% of older adults, 19 of whom approximately two-thirds have functional MR. 1 Among those with functional MR, 60% are of ischemic etiology. 1 , 20 This already high number of patients with severe iMR seeking treatment is likely to further increase with the recent Food and Drug Administration approval of the MitraClip for severe secondary MR, 21 similar to the impact of the adoption of transcatheter aortic valve replacement and its “halo” effect on surgical aortic valve replacement volume. 22 In multidisciplinary evaluation, the practical use of our risk stratification algorithm may be as the first broad-stroke identification of the low-risk group, which is expected to do very well from surgery, and separating them from the high-risk group, which likely would have poor surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mori et al suggested differences in outcomes between these two conditions, with A-FMR often associated with a relatively better prognosis. 43) Surgical interventions still have played a crucial role in the treatment of both V-FMR and A-FMR. The nuances in surgical outcomes underscore the necessity of distinguishing between V-FMR and A-FMR in clinical practice.…”
Section: Discussionmentioning
confidence: 99%